Evaluation of the PCR Method for the Diagnosis of Cutaneous Leishmaniasis in AL Hawija District, Kirkuk, Iraq - Husain F. Hassan1, Moath M. Salman1, Burhan M. Mohammed1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Males (191) and females (229) with skin lesions were enrolled in this investigation with the highest incidence of the disease in both sexes being in the age group (0-5) years . The clinical features of the lesions were covered by firmly adherent crust and some were edematous. By using classical microscopic examinations, the amastigotes were detectable in 143 cases out of 200 lesion samples. On the other hand , the use of specific PCR system and DNA sequences provided evidence that Leishmania tropica is the only etiologic agent of cutaneous leishmaniasis in AL Hawija district, Kirkuk province, Iraq.